An uncommon manifestation of COVID-19 pneumonia on CT scan with small cavities in the lungs: A case report. Issue 28 (10th July 2020) - Chen, Jinqing; Peng, Song; Zhang, Bangjun; Liu, Zhifeng; Liu, Lang; Zhang, Wendy
Abstract: Rationale: Chest computed tomography (CT) scans play a key role in diagnosing and managing of COVID-19 pneumonia. The typical manifestations of COVID-19 pneumonia on a chest CT scan are ground glass opacities, consolidation, nodules, and linear opacities. It can be accompanied by a "crazy-paving" pattern, air bronchograms, pleural hypertrophy, and pleural effusion. However, no literature has reported a case with cavities in the lungs. Patient concerns: A 34-year-old male patient complained of fever, cough, fatigue, myalgia, diarrhea, headache, and dizziness for 2 weeks. This patient is living in Xiaogan, a city around Wuhan, and he had contact with a patient with COVID-19 pneumonia from Wuhan <14 days before he had fever. Diagnosis: A nucleic acid test by rRT-PCR returned positive on a pharyngeal swab, confirming the diagnosis of COVID-19 pneumonia. Interventions: Isolation antiviral treatment. Outcomes: After 19 days of isolation and antiviral treatment, his temperature returned to normal and the symptoms were relieved. The laboratory results also were returning to normal levels. The chest CT scan showed that the acute inflammation had subsided significantly. With 2 consecutive novel coronavirus nucleic acid tests had returned negative, the patient was discharged from the hospital and sent to a government designated hotel for quarantine observation. The unique chest CT manifestation in this case was the small cavities in both lungs during the absorption phase of this disease. These small cavities developed into consolidated nodules with clear edges and gradually shrank or disappeared. Lessons: Although 2 consecutive nucleic acid tests returned negative in this patient, the small cavity changes in the lungs were observed, so the patient was quarantined for 14 days. However, follow-up CT after the first 14 days' quarantine showed new small cavity changes on the lungs, a further 14 days of quarantine was recommended. Therefore, in some COVID-19 cases, even if the nucleic acid tests turns negative, the disappearance of lung lesions may take a long time. The repeated chest CT scan plays an important role in the diagnosis and evaluation of the recovery of COVID-19.